Actividades lúdicas en el aprendizaje significativo de los estudiantes de cuarto año de básica de la escuela de educación básica “Gran Colombia” parroquia Puerto Pechiche, cantòn Puebloviejo, provincia los Ríos. - Moreira Córdova, Glenda Mariuxi (2017)
The present research work with the theme; Playful activities in the meaningful learning of the students of fourth year of Basic Education of the "Gran Colombia" Basic Education school, is of very important character because the teacher when using the ludic activities allows to turn the classes efficient, fun, where the exchange knowledge, ideas and learning. Through the game you will not only have fun, but you will have confidence with your teacher, who will communicate, relate to your classmates and you will gain meaningful learning. In this research work was provided with information on study variables such as: play activities and meaningful learning, they established an overall goal which is; To determine the play activities that affect the significant learning in the fourth year students, and three specific ones. A questionnaire was also used to answer questions that were answered voluntarily by teachers and students of the institution where the research was carried out, the respective conclusions were obtained and some recommendations were given. As a proposal, a guide to play activities was developed for teachers to promote meaningful learning for fourth year students.